2003
DOI: 10.1097/00044067-200302000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Patients With a Left Ventricular Assist Device

Abstract: As more patients have a diagnosis of end-stage heart failure, nurses are more likely to encounter the use of left ventricular assist devices (LVADs). Currently, LVADs are used as a bridge to cardiac transplantation. However, current research suggests that LVADs may be used as destination therapy for those unable to undergo cardiac transplantation. The technology has been developed to sustain life, but what is the impact of technology on the quality of life? This article reviews current research on the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Moreover, coping by their families and significant others can influence the patients' coping in positive or negative ways [15]. Families of VAD and HTX vad patients face frequently a sudden onset of the illness [16], whereas HTX patients' families often have time to adapt to the upcoming operation. The number of patients as well as the number of partners and families who need supportive psychotherapy increases with the complexity of distressing factors and the magnitude of the emotional burden.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coping by their families and significant others can influence the patients' coping in positive or negative ways [15]. Families of VAD and HTX vad patients face frequently a sudden onset of the illness [16], whereas HTX patients' families often have time to adapt to the upcoming operation. The number of patients as well as the number of partners and families who need supportive psychotherapy increases with the complexity of distressing factors and the magnitude of the emotional burden.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Savage reported that patients' limitations after LVAD implantation were not related to physical function, because the population examined had improved physical function, including increased exercise endurance and physical well-being. 22 The main concerns were related to potential device failure, infection and social functioning.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yet other studies have reported patients coping and accepting the situation of living with an implantable LVAD. In those studies, 22,23,27 investigators reported that patients who had a good sense of humor, engaged in diversional activities, developed a routine, took medications for anxiety and depression, and had a strong support system (ie, family, church, and health care team) successfully coped with the prolonged hospitalizations, boredom, and realities of living with the LVAD. Notably, the frequent interactions with the recipient's support system was an effective coping strategies reported by 40 adults at 3 months after the LVAD implant.…”
Section: Early Adjustment Stagementioning
confidence: 99%